The concept of organizational flexibility - some theoretical and empirical issues - Osbert-Pociecha, Grażyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
In this article presenting the results of the research project, an attempt was made to conceptualize the notion of the organizational flexibility, applying for this purpose the hitherto literary works on the subject and verifying understanding and evaluation of managing flexibility by the practitioners in the field of economics
Argumenta Oeconomica, 2008, No 2 (21), s. 79-108
Keywords: flexibility; conceptual framework; results of survey; zarządzanie przedsiębiorstwem; elastyczność organizacji; weryfikacja wiedzy